Cytotoxic cytochalasans from cultures of the fungus Metarhizium brunneum TBRC-BCC 79240. Issue 16 (4th April 2023) - Kornsakulkarn, Jittra; Auncharoen, Patchanee; Khonsanit, Artit; Boonyuen, Nattawut; Thongpanchang, Chawanee
Abstract : Fourteen new cytochalasans, brunnesins A–N (1–14 ), along with eleven known compounds, were isolated from the culture extracts of the insect pathogenic fungus Metarhizium brunneum strain TBRC-BCC 79240. Abstract : Fourteen new cytochalasans, brunnesins A–N (1–14 ), along with eleven known compounds, were isolated from the culture extracts of the insect pathogenic fungus Metarhizium brunneum strain TBRC-BCC 79240. The compound structures were established by spectroscopy, X-ray diffraction analysis, and electronic circular dichroism. Compound 4 exhibited antiproliferative activity against all cell lines tested (mammalian), with 50% inhibition concentration (IC50 ) values ranging from 2.09 to 16.8 μg mL −1 . Compounds 6 and 16 were shown to be bioactive only against non-cancerous Vero cells (IC50 4.03 and 0.637 μg mL −1, respectively) whereas compounds 9 and 12 were bioactive only against NCI-H187 small-cell lung cancer cells (IC50 18.59 and 18.54 μg mL −1, respectively). Compounds 7, 13, and 14 showed cytotoxicity against NCI-H187 and Vero cell lines with IC50 values ranging from 3.98–44.81 μg mL −1 .